Physiotherapy Management with Infrared, Transcutaneous Electrical Nerve Stimulation, and Nerve Tendon Gliding Exercise in Dextra Carpal Tunnel Syndrome Cases - Fressica, Amanda Rilya; Amanati, Suci (CV. Publikasi Indonesia, 2025)
Carpal tunnel syndrome (CTS) is a peripheral nerve disease caused by compression of the median nerve in the carpal canal, where the canal is limited by the carpal bone and transverse ligament. Carpal tunnel syndrome arises when the median nerve is compressed within the channel of the wrist. Symptoms caused by CTS can lead to functional impairment of the hand, while most human work involves using the hands, resulting in disruption of daily activities. Therefore, managing CTS patients—one of which is through physiotherapy treatment—is important. Providing physiotherapy interventions using Infrared aims to improve blood circulation, reduce pain, and increase muscle relaxation; Transcutaneous Electrical Nerve Stimulation (TENS) aims to reduce pain, increase muscle strength, and improve hand function. This scientific paper is a case study, presenting patient cases and collecting data through the physiotherapy process. The modalities administered are Infrared, TENS, and Nerve Tendon Gliding Exercise. After physiotherapy was performed four times, the results showed a decrease in pain, a decrease in paraesthesia/tingling, an increase in the range of joint motion, an increase in muscle strength, and an improvement in functional activity ability as measured by the WHDI index. Physiotherapy management with Infrared, Transcutaneous Electrical Nerve Stimulation, and Exercise modalities performed over four therapy sessions in cases of Carpal Tunnel Syndrome Dextra can reduce pain and paraesthesia/tingling, increase the range of joint motion, enhance muscle strength, and improve functional activity as indicated by the WHDI index.